2006
DOI: 10.1063/1.2213958
|View full text |Cite
|
Sign up to set email alerts
|

Silver-halide segmented cladding fibers for the middle infrared

Abstract: There is a wide interest in single-mode optical fibers for the middle infrared range of 3–30μm. These fibers will be useful for a variety of applications such as spatial filtering and interferometry. However, many technical and theoretical problems hindered the development of such fibers. Segmented cladding fibers may make it possible to combine an extremely large core area and single mode operation over a large spectral range. The design parameters may accurately control the optical properties of such fibers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…As we can see from the summary, Fig. 6, intensity profile of FM shows that smaller MFR would anticipate higher nonlinear effects on incidence, whereas NA of an angularly segmented cladding can be defined by replacing n 2 with n eff [33], thus NA = n 2 1 − n 2 eff , and its plot as a function of wavelength is shown in Fig. 7.…”
Section: Mode Field Radius (Mfr) and Numerical Aperture (Na)mentioning
confidence: 99%
“…As we can see from the summary, Fig. 6, intensity profile of FM shows that smaller MFR would anticipate higher nonlinear effects on incidence, whereas NA of an angularly segmented cladding can be defined by replacing n 2 with n eff [33], thus NA = n 2 1 − n 2 eff , and its plot as a function of wavelength is shown in Fig. 7.…”
Section: Mode Field Radius (Mfr) and Numerical Aperture (Na)mentioning
confidence: 99%
“…[14][15][16][17][18] Under this circumstance, researches on the rare earth doped segmented-cladding polymer optical fibers (SCPOF) were started in our group based on our previous work on rare earth doped multi-mode POF. [19][20][21][22][23][24][25][26][27][28] In this work, a model for selection of suitable core and cladding polymers for SCPOF is proposed in terms of the physical principle and requirements for a preform of SCPOF.…”
Section: Introductionmentioning
confidence: 99%
“…A new design of fiber structure called segmented‐cladding fiber (SCF) gave another way to fabricate SMFs, which has a uniform core of a high refractive index and a cladding with alternating angularly regions of high and low refractive indices 12, 13. For it's unique structure, especially for the single‐moded operation realized in a large core diameter, application of SCF concept in POF has attracted much attention in recent years 14–18. Under this circumstance, researches on the rare earth doped segmented‐cladding polymer optical fibers (SCPOF) were started in our group based on our previous work on rare earth doped multi‐mode POF 19–28.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of SCF, which contains alternate high-and low-index segments in the angular direction in the cladding, makes it difficult to fabricate it with conventional optical fiber fabrication technologies. 4 It is very difficult to fabricate the SCF in silica glass as it is a comparatively hard material and not easy to shape into segments of the desired geometry. [4][5][6][7] Yeung et al experimentally demonstrated fabrication of polymer SCF and used two methods to fabricate the fiber.…”
Section: Introductionmentioning
confidence: 99%